System-Wide Analysis Unravels the Differential Regulation and In Vivo Essentiality of Virulence-Associated Proteins B and C Toxin-Antitoxin Systems of Mycobacterium tuberculosis. (24th February 2018) - Agarwal, Sakshi; Tiwari, Prabhakar; Deep, Amar; Kidwai, Saqib; Gupta, Shamba; Thakur, Krishan Gopal; Singh, Ramandeep
Abstract : In the present study, we show that ectopic expression of virulence-associated protein C (VapC) toxins results in morphological changes and growth arrest. These toxins are differentially induced and also regulated at the posttranscriptional level. The present study highlights that VapBC toxin-antitoxin systems contribute to mycobacterial pathogenesis. Abstract: Toxin-antitoxin (TA) systems are bicistronic genetic modules that are ubiquitously present in bacterial genomes. The Mycobacterium tuberculosis genome encodes 90 putative TA systems, and these are considered to be associated with maintenance of bacterial genomic stability or bacterial survival under unfavorable environmental conditions. The majority of these in M. tuberculosis have been annotated as belonging to the virulence-associated protein B and C (VapBC) family. However, their precise role in bacterial physiology has not been elucidated. Here, we functionally characterized VapC toxins from M. tuberculosis and show that overexpression of some homologs inhibits growth of Mycobacterium bovis bacillus Calmette-Guérin in a bacteriostatic manner. Expression profiling of messenger RNA revealed that these VapC toxins were differentially induced upon exposure of M. tuberculosis to stress conditions. We also unraveled that transcriptional cross-activation exists between TA systems in M. tuberculosis . This study provides the first evidence for the essentiality of VapBC3 and VapBC4 systems in M. tuberculosis virulence.